Book review: laut bercerita, the sinking of untold tales - Wajdi, Majid; Putri, Erma Artajosi; Putri, Ni Putu Radha Savitri Maheswari; Ariyanti, Ni Luh Novia; Sinanditha, I Gede Bagus Ananda; Maharani, Anak Agung Radha Regita; Dewi, Ni Komang Mayang Saptariyasa; Riswana, I Gede Maryo Kanka (Yayasan Mitra Persada Nusantara, 2023)
Leila S. Chudori or full Leila Salikha Chudori (born December 12, 1962) is an Indonesian writer who has written works such as short stories, novels, and television drama scenarios. A few notes about Leila who was selected to represent Indonesia to receive a scholarship to study at